Atlas and Anatomy of PET/MRI, PET/CT and SPECT/CT - Kim, E. Edmund; Murad, Vanessa; Paeng, Jin-Chul.; Cheon, Gi-Jeong.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
The Atlas and Anatomy of PET/MRI, PET/CT, AND SPECT/CT, Second Edition features cross-sectional anatomy to assist in proper interpretation of images generated from PET/MRI, PET/CT, and SPECT/CT applications. At the forefront of nuclear and molecular imaging, hybrid imaging improves data acquisition for diagnosis and treatment. Simultaneous evaluation of anatomic and metabolic information about normal and abnormal processes addresses complex clinical questions and elevates confidence in scan interpretations. Extensively illustrated with high-resolution PET/MRI, PET/CT and SPECT/CT images, the atlas offers precise morphologic information for the whole body, including specific regions such as the head and neck, abdomen, and musculoskeletal system. Updated with teaching cases and many recent non-FDG PET cases, Atlas and Anatomy of PET/MRI, PET/CT, AND SPECT/CT, Second Edition is a unique resource for physicians and residents in nuclear medicine, radiology, oncology, neurology, and cardiology.
1. Atlas and Anatomy of PET/MRI -- 2. Atlas and Anatomy of PET/CT -- 3. Atlas and Anatomy of SPECT/CT. .
Keywords: Radiology; Nuclear medicine; Internal medicine; Radiology; Nuclear Medicine; Internal Medicine; Multimodal Imaging; Anatomy; Magnetic Resonance Imaging; Positron-Emission Tomography; Tomography, X-Ray Computed; Atlases